THEORETICAL FOUNDATIONS OF THE DEVELOPMENT OF THE DIGITAL ECONOMY - Ph.D. Kilicheva Farida Beshimovna (Journals Park Publishing, 2024)
This article will review and examine the theoretical foundations of the digital economy. In the ever-evolving landscape of the 21st century, the global economy has undergone profound transformations driven by technological advancements, globalization, and shifting geopolitical dynamics. This development brings both opportunities and challenges, requiring countries, businesses, and individuals to adopt new strategies to navigate the complexities of the modern economy. From digitalization to sustainable practices, today's economic strategies are multifaceted, reflecting a rapidly changing world.
Keywords: Digitalization, information and communication technology, innovation theory, network effects, platform economy, globalization, digital infrastructure, cloud computing.